Imperfect twinning: a clinical and ethical dilemma - Denardin,Daniela (2013)
OBJECTIVE To review the history, epidemiology, etiology, gestational aspects, diagnosis and prognosis of imperfect twinning. DATA SOURCES Scientific articles were searched in PubMed, SciELO and Lilacs databases, using the descriptors "conjoined twins", "multiple pregnancy", "ultrasound", "magnetic resonance imaging" and "prognosis". The research was not delimited to a specific period of time and was supplemented with bibliographic data from books. DATA SYNTHESIS: The description of conjoined twins is legendary. The estimated frequency is 1/45,000-200,000 births. These twins are monozygotic, monochorionic and usually monoamniotic. They can be classified by the most prominent fusion site, by the symmetry between the conjoined twins or by the sharing structure. The diagnosis can be performed in the prenatal period or after birth by different techniques, such as ultrasound, magnetic resonance imaging and echocardiography. These tests are of paramount importance for understanding the anatomy of both fetuses/children, as well as for prognosis and surgical plan determination. CONCLUSIONS Although imperfect twinning is a rare condition, the prenatal diagnosis is very important in order to evaluate the fusion site and its complexity. Hence, the evaluation of these children should be multidisciplinary, involving mainly obstetricians, pediatricians and pediatric surgeons. However, some decisions may constitute real ethical dilemmas, in which different points should be discussed and analyzed with the health team and the family.